The Struggle for the Meaning of Islam in the Post-Truth Era: Critical Discourse Analysis of Narratives on the Hidayatullah.com Portal - Arfan, Arfan; Hatta, Juparno; Azlan, Ulfatmi (FIKRAH, 2025)
The effectiveness of new media has transformed Islamic preaching into the digital space, creating a new landscape for Islamic discourse. This phenomenon occurs in the post-truth era, when emotions and subjective beliefs influence public opinion more than facts. Hidayatullah.com, a popular Islamic portal among Indonesian Muslims, actively produces Islamic narratives. However, the texts it publishes often reflect certain ideological interests and social positions. This study examines the relationship between power and ideology in Hidayatullah.com's representation of Islam. The study employs Norman Fairclough's Critical Discourse Analysis (CDA) approach, enriched with Foucault's readings. Data were obtained through a literature review of Islamic-themed texts in the portal's article section. The results show that Hidayatullah.com functions as a discursive agent that frames Islamic issues in a way that reinforces conservative ideology. The portal uses discourse to reinforce religious narratives and identities in line with its ideological orientation. This study contributes to a critical understanding of the formation of religious meaning and authority in the post-truth era.